2020
DOI: 10.7150/ijbs.40516
|View full text |Cite
|
Sign up to set email alerts
|

TASP1 Promotes Gallbladder Cancer Cell Proliferation and Metastasis by Up-regulating FAM49B via PI3K/AKT Pathway

Abstract: The highly conserved protease TASP1 not only takes part in critical site-specific proteolysis, but also plays an important role in numerous liquid and solid malignancies. However, the TASP1 expression and its biological regulation function in malignant gallbladder carcinoma (GBC) remain fully unknown. Here we observed that TASP1 levels were substantially overexpressed in GBC samples compared with non-tumor tissues. High TASP1 level was closely associated with T stage and metastasis, and was also correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…29 PI3K/AKT signaling pathway is involved in cell proliferation, differentiation, apoptosis and other cellular processes. [30][31][32] Meanwhile, the PI3K/AKT signaling pathway takes part in tumor metastasis. 33 Intriguingly, it has been reported that PI3K/ AKT signaling pathway can be regulated by lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…29 PI3K/AKT signaling pathway is involved in cell proliferation, differentiation, apoptosis and other cellular processes. [30][31][32] Meanwhile, the PI3K/AKT signaling pathway takes part in tumor metastasis. 33 Intriguingly, it has been reported that PI3K/ AKT signaling pathway can be regulated by lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TASP1 promoted cell proliferation both in vivo and in vitro, as well as cell migration and invasion in vitro in GBC. 81 Interestingly, FAM49B was also overexpressed in GBC tissue as compared with non-tumor tissue and was identified to have a positive association with TASP1 expression in GBC. TASP1 can upregulate FAM49B, thus promote the proliferation and migration of GBC cells by activating the PI3K/AKT signaling pathway.…”
Section: Taspase 1 and Family With Sequence Similarity 49 Member Bmentioning
confidence: 92%
“…The highly conserved protease taspase 1 (TASP1) is a non-oncogene addiction protease in various types of liquid and solid tumors. 81,135 Family with sequence similarity 49 member B (FAM49B) has recently been found to play a role in suppressing cancer cell proliferation and invasion in pancreatic ductal adenocarcinoma, 136 which indicates that it may be associated with tumor progression. A recent study showed that TASP1 expression was significantly higher in GBC tissue than nontumor tissue.…”
Section: Taspase 1 and Family With Sequence Similarity 49 Member Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Several inhibitors targeting the PI3K/AKT/mTOR pathway, including A66, Wortmannin, and LY294002, have been demonstrated to inhibit GBC cell proliferation, migration, and invasion both in vitro and in vivo. 215 217 In addition, rapamycin, RAD001, and AZD8055 reported by Leal et al 218 were able to block mTOR and inhibit the growth and migration of GBC cells in vitro. In a transgenic mouse model, rapamycin can also inhibit the incidence of GBC.…”
Section: Targeted Therapy Of Gbcmentioning
confidence: 95%